Wound healing and skin integrity : principles and practice - Flanagan, Madeleine (Wiley-Blackwell, A John Wiley & Sons, Ltd. Publication, 2013)
Useful resources; References; 5 Principles of Wound Management; Introduction; Principles of wound management; Effective wound management; Controlling bacterial burden: wound cleansing; Temperature; Types of wound cleanser; Method of cleansing; Controlling bacterial burden: wound debridement; Autolytic debridement; Enzymatic debridement; Biosurgical debridement; Mechanical debridement; Sharp debridement; Conservative sharp debridement; Surgical debridement; Hydrosurgical debridement; Ultrasound (acoustic pressure wound therapy); Regulating moisture balance; Wound dressings.